Comparison of supporters and hooligans in the Czech Republic. The example of the football club Slavia Prague - Scholz, P.; Vespalec, T. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
Football is the most global sport and a top ten sport in all countries. Given the long history of spectators and consumers of sports events, it is not a surprising the fact that there have also been serious manifestations of spectators aggression. The aim of this paper is to analyze the relationship between supporters’ and hooligans’ verbal and other expressions and their violent behavior at football stadiums in the Czech Republic. Primary data were collected by a questionnaire survey (PAPI method) mainly at the Eden stadium in 2015 and 2016. A total of 95 respondents (age 23.66 ± 10.29) participated in this pilot study. All of respondents were attending in a stand of home team supporters. Results confirmed that 100% of hooligans did not consider a serious issue the fights arranged by them outside the stadium. 54.32% of the supporters considered that the most serious problems were the damages caused to the stadium and other disturbances.